Application of Path Analysis in Determining Factors Affecting the Learning Outcomes of Elementary School Teacher Education Students at HKBP Nommensen University, Pematangsiantar - Suryadi, Yeanny; Sinaga, D.Yuliana; Sidabutar, Yanti Arasi; Mulyono, Mulyono; Syahputra, Edi (Information Technology and Science (ITScience), 2026)
This study aims to analyze the direct and indirect influence of the role of parents, the role of lecturers, and learning motivation on the learning outcomes of Elementary School Teacher Education (PGSD) students at UHKBPNP using the Path Analysis method. Data processing was carried out using the SPSS program. The prerequisite test showed that the model met the assumption of normality and was free from multicollinearity. The findings showed: (1) The role of parents did not have a significant direct influence on learning outcomes. (2) The role of lecturers had a significant direct influence on learning outcomes. (3) Learning motivation had a significant direct influence on learning outcomes. Furthermore, the analysis revealed that the role of parents and the role of lecturers indirectly influenced learning outcomes significantly through the mediating role of learning motivation. This study concluded that learning motivation functions as a central psychological mechanism that bridges the influence of environmental factors (the role of parents and lecturers) on improving student learning outcomes. Environmental support becomes optimal only when it succeeds in fostering strong internal motivation in students.